2012
DOI: 10.1080/1461670x.2011.578940
|View full text |Cite
|
Sign up to set email alerts
|

Public Service News on the Web

Abstract: This article provides an empirical basis for discussions of public service news on the Web. Through innovative use of computer-assisted data gathering and structuring, and a combination of quantitative methods, we present the results from a large-scale analysis of the online news content of the Norwegian Broadcasting Corporation, NRK. The study reveals not only specifics of the online news genre, but also the dual role of NRK as a public service broadcaster. nrk.no fulfils regional content provisions by having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
1
16
0
2
Order By: Relevance
“…Content analysis online is, mildly put, challenging. Several researchers have stressed the general difficulties of analyzing the content of a liquid medium where traditional content analysis offers very few, if any, suitable methodologies (Deuze, 2008;Karlsson, 2012;Sjøvaag et al, 2012). Moreover, in order to protect their business, media organizations utilize various measures to prevent unauthorized downloading of their content from online archives (Murphy, Hashim, & O'Connor, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Content analysis online is, mildly put, challenging. Several researchers have stressed the general difficulties of analyzing the content of a liquid medium where traditional content analysis offers very few, if any, suitable methodologies (Deuze, 2008;Karlsson, 2012;Sjøvaag et al, 2012). Moreover, in order to protect their business, media organizations utilize various measures to prevent unauthorized downloading of their content from online archives (Murphy, Hashim, & O'Connor, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Chang et al have in two studies (Chang & Himelboim, 2009;Chang et al, 2012) singled out financial considerations as the sole factor having a negative impact on (external) hyperlinking practices, arguing that it is 'unthinkable' (Chang & Himelboim, 2009, p. 144) for commercial websites to direct readers out of their own online space. Advertising is dependent on exposure and external links would thus negatively affect the bottom line, especially since competition increases online (Himelboim, 2010;Sjøvaag et al, 2012;Weber & Monge, 2011). Although research has found that journalists are positive toward links and think they help to create context, in the end hyperlinking is constrained by financial considerations (Chang et al, 2012;Coddington, 2012).…”
Section: Factors Conditioning Hyperlinkingmentioning
confidence: 95%
See 2 more Smart Citations
“…Westwood et al (2013) examined 3.2 million articles to identify which foreign countries and regions receive most coverage in U.S. newspapers. Sjøvaag et al (2012) used computer-assisted data gathering and structuring to study the online news content of the Norwegian public service broadcaster. Even social media studies need not be about social media as a social phenomenon.…”
Section: Related But Differentmentioning
confidence: 99%